Corporate Entrepreneurship of SMEs and Business Management Strategies in the Digital Era - Inayati Zahro, Nafi'; Fiati, Rina; Hadapining Radja Kusumodestoni, R. (KnE Social Sciences, 2024)
Micro, small, and medium enterprises (MSMEs) play a strategic role in enhancing Indonesia’s economy. MSMEs have demonstrated resilience in addressing economic crisis that impacted the Indonesian economy, leading to the bankruptcy of numerous large companies. Yogas Delima trading business and CV Alammu produce the herbal syrup, specifically the Parijotho syrup product, which stands out as a superior offering characteristic of Kudus city. However, the Department of Industry, Trade, Cooperatives, and SMEs in Kudus Regency has not extensively promoted these two herbal syrup beverage products. MSMEs encounter primary challenges such as a lack of guidance, organizational weaknesses, suboptimal guidance and management strategies, low human resources capacity, suboptimal raw material management suboptimal, and conventional marketing practices. The purpose of this service is to enhance the development of SMEs by increasing competitiveness and improving product quality through the application of information technology in E-Commerce and E-Business. Additionally, it addresses aspects of human resources, raw materials, management, and production improvements. The implementation method includes (1) the initial observation stage, (2) the needs analysis stage, (3) the training and mentoring stage, (4) the follow-up stage, and (5) the evaluation stage. Keywords: entrepreneurship, business, management, digital, SME